Occurrence of apocrine secretion in the larval gut epithelial cells of aedes aegypti L., Anopheles albitarsis Lynch-Arribálzaga and Culex quinquefasciatus Say (Diptera: Culicidae): A defense strategy against infection by Bacillus sphaericus Neide? - Oliveira, Caroline D.; Tadei, Wanderli Pedro; Abdalla, Fábio Camargo (Neotropical Entomology, 2009)
Cell hypertrophy was the first reaction of the gut epithelial cells of Aedes aegypti (L.), Anopheles albitarsis (Lynch-Arribálzaga) and Culex quinquefasciatus (Say) to the toxins of strains 2362 and S1116 of Bacillus sphaericus, as cells had an increase of intracellular secretory activity. Soon after the cell hypertrophy developed, vesicles were formed at the cell apical portion, which detached with the plasma membrane, characterizing a type of apocrine secretion like. The first pathway of contamination of the mosquito larvae by these bacteria is through the gut, by feeding. Depending on the species of Culicidae and on the bacterial strain used, the hypertrophy of the gut epithelium occurred between 5 and 15 min after exposure to the contaminated environment. The second aspect observed after hypertrophy was the increase in apocrine secretion. The basophilic vesicles that detached from the cells remained between the peritrophic membrane and the gut lumen, such vesicles were filled with material of unknown nature. The gut posterior region showed secretory activity in both control and treated larvae, being much more intense in bacteria-exposed larvae. There were remarkable differences in the epithelial cell reaction according to the toxins of the two bacterial strains, but C. quinquefasciatus was the most susceptible. Differences in the gut cell reactions to the toxins produced by the two bacterial strains are discussed.
Ocorrência de Secreção Apócrina nas Células Epiteliais do Intestino de Larvas de Aedes aegypti L., Anopheles albitarsis Lynch-Arribálzaga e Culex quinquefasciatus Say (Diptera: Culicidae): Um Mecanismo de Defesa contra Infecção Causada por Bacillus sphaericus Neide?
Keywords: Aedes Aegypti; Anopheles Albitarsis; Bacillus Sphaericus; Bacteria (microorganisms); Culex Pipiens Quinquefasciatus; Culicidae; Diptera